(untitled) (Research, Society and Development, 2021)
This paper aims to present a field study on childhood depression and the teaching-learning process, seeking, more specifically, to discuss the importance of the teacher’s role. Given its recent evidence in childhood, childhood depression often goes unnoticed. And because it affects many aspects of the child’s life, including the teaching-learning process, we assume that the teacher can play a fundamental role in identifying the child affected by depression. Therefore, this has been a challenge faced by several teachers involved in the teaching and learning process in general. For this, we carried out a field research, with the application of a questionnaire through Google Forms to 29 students in the last semester of the pedagogy course at a public university in the state of Goiás, seeking to understand the knowledge of future teachers on the subject. The research results show that although they believe it is important that their training includes basic knowledge about childhood depression, most students, who are in the last semester of the pedagogy course and, therefore, will soon be in the classroom, assess the guidance received on the subject as insufficient, therefore, they do not feel prepared to identify or deal with children affected by the disease. Therefore, it is necessary to have greater knowledge of the disorder, its symptoms and how it occurs in childhood. Thus, you will be able to help many of your students to receive greater care and alert those responsible so that they can seek adequate professional help and the child can receive treatment as soon as possible. The sooner it is referred to professionals, the more positive results are manifested in the treatment and the damage to the child’s life, as well as in the teaching-learning process, can be significantly minimized.